2022
DOI: 10.1021/acs.energyfuels.2c03261
|View full text |Cite
|
Sign up to set email alerts
|

New Model of Oil Migration in Shale Nanopores Considering Microscopic Deformation Induced by Stress and Pore Pressure

Abstract: During the exploitation of shale oil, the stress and pore pressure of the reservoir generally change, resulting in the deformation of the shale pore structure, which affects the oil migration in shale nanopores. Establishing an oil migration model and a permeability model that take into account the effects of reservoir stress and pore pressure is important for the numerical simulation shale oil development. In this paper, a new oil migration model in inorganic (IM) and organic (OM) nanopores of shale and a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(196 reference statements)
0
3
0
Order By: Relevance
“…Due to the small average free range of shale oil molecules, many scholars believe that the Knudsen number of shale oil flowing in nanopores is Kn < 0.1; therefore, the current study regarded the flow of shale oil in nanopores as following the continuity assumption [30,46]. However, actual shale oil flow is higher than the value calculated using the traditional Darcy's law and continuity assumption because diffusion and slip phenomena, etc., need to be considered in such nanopores [12,47,48]. Some scholars are now correcting the traditional Darcy's formula by introducing the apparent permeability [13,49].…”
Section: Oil Flow Mechanism In Shalesmentioning
confidence: 99%
“…Due to the small average free range of shale oil molecules, many scholars believe that the Knudsen number of shale oil flowing in nanopores is Kn < 0.1; therefore, the current study regarded the flow of shale oil in nanopores as following the continuity assumption [30,46]. However, actual shale oil flow is higher than the value calculated using the traditional Darcy's law and continuity assumption because diffusion and slip phenomena, etc., need to be considered in such nanopores [12,47,48]. Some scholars are now correcting the traditional Darcy's formula by introducing the apparent permeability [13,49].…”
Section: Oil Flow Mechanism In Shalesmentioning
confidence: 99%
“…China is rich in shale oil resources and ranks third in the world, , which is an important field for the development of China’s petroleum resources. Due to the low porosity and permeability of shale oil reservoirs, single wells usually have no natural productivity, or the natural productivity is below the lower limit of industrial oil flow, and the reservoirs must be fractured before commercial development of shale oil can be realized . After fracturing, the initial production of a single well is significantly increased, but the reservoir pressure decays quickly, and the stable production effect is not good, with the primary recovery ratio usually below 10%. There is still a large amount of oil retained in the pores of the shale reservoir, which has a huge potential for development.…”
Section: Introductionmentioning
confidence: 99%
“…7−9 This makes it easier for more shale oil to flow to the wellbore and efficiently enhances the recovery. 10,11 Meanwhile, CO 2 used can also be sequestered in shale reservoirs in the form of dissolution, trapping, and mineralization. 12−15 The issue that the geochemical and physical interaction between SC-CO 2 and shale affects the shale oil yield and the stability of shale as a caprock cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant investigations have shown that supercritical carbon dioxide (SC-CO 2 ) can significantly enhance the recovery of shale reservoirs. When the pressure and temperature of CO 2 reach a certain condition (generally P ≥ 7.38 MPa, T ≥ 31.1 °C), it will enter the supercritical phase. Thanks to its high density, minimal viscosity, and excellent diffusivity, supercritical carbon dioxide (SC-CO 2 ) easily mixes with crude oil and can effectively lower its viscosity. This makes it easier for more shale oil to flow to the wellbore and efficiently enhances the recovery. , Meanwhile, CO 2 used can also be sequestered in shale reservoirs in the form of dissolution, trapping, and mineralization. …”
Section: Introductionmentioning
confidence: 99%